2002
DOI: 10.1046/j.1365-2958.2002.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of tachyzoite to bradyzoite differentiation mutants in Toxoplasma gondii reveals a hierarchy of gene induction

Abstract: Summary Developmental switching in Toxoplasma gondii, from the virulent tachyzoite to the relatively quiescent bradyzoite stage, is responsible for disease propagation and reactivation. We have generated tachyzoite to bradyzoite differentiation (Tbd−) mutants in T. gondii and used these in combination with a cDNA microarray to identify developmental pathways in bradyzoite formation. Four independently generated Tbd− mutants were analysed and had defects in bradyzoite development in response to mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 61 publications
5
117
1
2
Order By: Relevance
“…We note that these TgPUS1-deficient parasites are insertional mutants (TBD5, isolated by Singh et al 2002 and characterized by Anderson et al 2009), rather than TgPUS1 knockouts. Furthermore TgPUS1-deficient parasites incubated under bradyzoite conditions for 84 h are not able to differentiate; therefore, TgPUS1-deficient "bradyzoites" express subsets of both tachyzoite and bradyzoite markers (Anderson et al 2009 and data not shown).…”
Section: Psi-seq Identifies Evolutionarily Conserved Sites Of Pseudoumentioning
confidence: 92%
See 3 more Smart Citations
“…We note that these TgPUS1-deficient parasites are insertional mutants (TBD5, isolated by Singh et al 2002 and characterized by Anderson et al 2009), rather than TgPUS1 knockouts. Furthermore TgPUS1-deficient parasites incubated under bradyzoite conditions for 84 h are not able to differentiate; therefore, TgPUS1-deficient "bradyzoites" express subsets of both tachyzoite and bradyzoite markers (Anderson et al 2009 and data not shown).…”
Section: Psi-seq Identifies Evolutionarily Conserved Sites Of Pseudoumentioning
confidence: 92%
“…To begin the identification of Ψ's in Toxoplasma, i.e., its predicted "pseudouridylome," we performed PSI-seq on tachyzoite and bradyzoite RNA isolated from wild-type parasites (specifically C32 parasites, a clone derived from a Type II Pru strain [Singh et al 2002]). Tachyzoites were grown in neutral pH and serum-rich conditions, while bradyzoite differentiation was induced using starvation (1% FBS) and high pH (8.0).…”
Section: Psi-seq Identifies Evolutionarily Conserved Sites Of Pseudoumentioning
confidence: 99%
See 2 more Smart Citations
“…This method of measuring differentiation is laborious and has numerous steps in which experimental variation could mask significant but subtle results. Flow cytometry can also be used to assess bradyzoite differentiation in parasites expressing GFP driven by a bradyzoite-specific promoter such as LDH2 but this method does not quantitate growth in parallel (Singh et al, 2002). Currently, there is no parasite that allows enzymatic quantitation of both growth and bradyzoite gene expression.…”
Section: Introductionmentioning
confidence: 99%